STRATEGI PENGEMBANGAN DESTINASI WISATA RIAM SOLAKNG DI DUSUN PETAI BEJAMBU KECAMATAN SENGAH TEMILA KABUPATEN LANDAK - Weny Juliana; Putri Tipa Anasi; Maria Ulfah (Jurnal Ilmiah Global Education, 2023)
This research is entitled Strategy for the Development of Riam Solakng Tourism Destinations in Petai Bejambu Hamlet, Sengah Temila District, Landak Regency. This study aims to describe the strategy for developing the Riam Solakng tourist destination in Petai Bejambu Hamlet, Sengah Temila District, Landak Regency. The method in this study is a qualitative descriptive with SWOT analysis to formulate a strategy for developing the Riam Solakng tourist destination. Data collection techniques used are observation, interviews and documentation. The results of the study show that Riam Solakng tourism is in quadrant II (3.06-2.86). The strategy offered for this research is a strategy for developing tourist destinations based on attractions, accessibility and amenities (3A) which supports diversification strategies in developing products and services that can be offered to tourists.